2013
DOI: 10.21161/mjm.51913
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and screening of antimicrobial activity of Micromonospora strains from Thai soils

Abstract: Aims: Rare actinomycete strains were isolated from mountain soils and island soil collected in Thailand. They were screened for antimicrobial activity and characterized for their secondary metabolites. Methodology and results: The strains were isolated by the standard dilution technique using starch casein nitrate agar. They were identified and characterized based on the phenotypic, chemotaxonomic and genotypic characteristics. The chemotaxonomic characteristics of ten isolates coincided with those of the genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Micromonospora chokoriensis was first isolated as a novel isolate from the sandy soil in Chokoria, Bangladesh 17 . Later, it was reported from the mountain soil in Thailand 10 and from the desert soils of Chile and China 11 , 12 . Previously a study 18 reported the isolation of M. chokoriensis strain B020 as an endophyte from wild medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micromonospora chokoriensis was first isolated as a novel isolate from the sandy soil in Chokoria, Bangladesh 17 . Later, it was reported from the mountain soil in Thailand 10 and from the desert soils of Chile and China 11 , 12 . Previously a study 18 reported the isolation of M. chokoriensis strain B020 as an endophyte from wild medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, about 65 species have been reported 9 from different environments such as soil, sediments, water, and root nodules 10 that are reported to produce antibiotics such as diazepinomicin, lomaiviticins A and B, lupinacidins A and B, netamicin, and tetrocarcin A 9 . Most recently, antimicrobial metabolites such as sagamycin, gentamicin, halomicin, ivermectin, mutamicin, and mycinamicin have also been identified in them 11 . Since this genus is second to Streptomyces as a source of novel metabolites 12 , new species from it remain a focus of research 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, most studies of microbes from Thai mangroves have focused on bacteria and yeast (Limtong et al, 2007(Limtong et al, , 2008Am-In et al, 2008Atipan et al, 2012;Songsumanus et al, 2013;Wongwongsee et al, 2013;Hwanhlem et al, 2014;H-Kittikun et al, 2015;Wanapaisan et al, 2018). Fungi from Thai mangroves, especially acid-tolerant fungi and their bioactive metabolites under conditions of acidic stress, have not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%